Transaction log analysis of author searching in a university library: Basis for improving OPAC retrieval results - Fresnido, Ana Maria B. (Animo Repository, 2022)
PurposeThis paper assesses the performance and functionality of the De La Salle University (DLSU) Library's OPAC through the use of transaction log analysis (TLA) particularly for author searches with no retrievals. DesignTLA was used to examine the data. Search queries were analyzed one by one to identify the reasons/errors behind author searches with no retrievals. Simulated searching for some of the queries wherein reasons for zero retrievals were difficult to determine were also performed. FindingsResults of the study revealed issues relating to the patrons' lack of awareness or familiarity on the use of the OPAC as well as its different features; non-existent of instructions on its clients about the two types of OPACs that the library has and which OPAC caters to the different sets of databases. Originality/ValueThe study conducted is a modest contribution to the field of library and information science in the Philippines, being the first study conducted assessing an OPAC's performance, functionality and design using TLA.